Lokalitas Penafsiran Kiai Abul Fadhol Senori Dalam Kitab Tafsir Al-Ayat Al-Ahkam - M. Lytto Syahrum Arminsa; Muhammad Munif (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2021)
This paper describes the locality of Kiai Abul Fadhol Senori’s interpretation in his book of commentaries entitled Al-Ayat Al-Ahkam. Kiai Abul Fadhol Senori is one of the scholars of the archipelago who was born in Tuban and has a deep religious scientific capacity, one of which is fiqh. His deep knowledge of fiqh prompted him to write a book of commentaries related to the laws of the Shari’a. Methodlogically, the writing of the book of Al-Ayat Al-Ahkam uses the tematic method (maudhu’i). Because the themes raised around the laws of the Shari’a, make this book of interpretation classified as a book with the pattern of ahkam interpretation. The systemics of writing fiqh books starting from the chapter of thahrah, prayer and so on. The data used in this study were sourced from the third copy of the commentary book and direct interviews with Mudjami’ Sulaiman, as a student and copyist of the book. In another, uniqueness of the book of interpretation of Al-Ayat Al-Ahkam is the locality of its interpretation. By using the tmatic-analytic deskriptive method, this paper find several findings regarding the locality of interpretation: first, the problem of determining the direction Qibla: second, the ability to carry outsocial activities after Friday prayers sucah as visits (tilik), takziah, gatherings. Basically, the emergence of local issues in an interpretation cannot be separated from the socio-cultural context of the community, therefore the struggle of the interpreter with the surronding community is a necessity.